2017
DOI: 10.1590/0103-8478cr20160921
|View full text |Cite|
|
Sign up to set email alerts
|

Ecogeography of Lippia rotundifolia Cham. in Minas Gerais, Brazil

Abstract: Lippia rotundifolia is a specie native to the Brazilian Cerrado, endemic to the Cadeia do Espinhaço mountain range. Due to the limited information about the species, the present study aimed to characterize the ecogeography, climate conditions and physical and chemical characteristics of the soil of Lippia rotundifolia in the state of Minas Gerais, Brazil. Thirteen sites were ecogeographically characterized: Parque Estadual Veredas do Peruaçu; Gigante; Rio do Peixe; AEP of Olhos D’água; Joaquim Felício; Parque … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…The low genetic diversity observed can be explained by the small population density, which made it impossible to keep sampling with the same distance between the individuals as sampled for Lippia origanoides (Suárez et al, 2008), where the authors reported that the sampling between individuals equidistant 1.2 Km, results in different genotypes. Another factor observed in this study was that the temperature may also have contributed to the genotypic adaptation of the plant (Vega-Vela & Sánchez, 2012;Meira, Martins, & Resende, 2017).…”
Section: Resultsmentioning
confidence: 75%
“…The low genetic diversity observed can be explained by the small population density, which made it impossible to keep sampling with the same distance between the individuals as sampled for Lippia origanoides (Suárez et al, 2008), where the authors reported that the sampling between individuals equidistant 1.2 Km, results in different genotypes. Another factor observed in this study was that the temperature may also have contributed to the genotypic adaptation of the plant (Vega-Vela & Sánchez, 2012;Meira, Martins, & Resende, 2017).…”
Section: Resultsmentioning
confidence: 75%
“…Adicionalmente, por ser uma espécie não cultivada, cuja exploração se dá de forma extrativista, torna-se extremamente vulnerável a erosão genética, sendo imprescindíveis estudos e ações que subsidiem trabalhos na área de conservação, domesticação e desenvolvimento de sistemas de cultivos (Silva, 2015). Nesse contexto, a ecogeografia é uma ferramenta de grande importância, pois permite predizer em que tipo de ambiente uma espécie nativa ocorre e, ainda, a sua adaptação aos fatores geográficos, edáficos e climáticos (Meira, 2017).…”
Section: Introductionunclassified